The Potential of Social Media as a Means of Online Business Promotion - Allyana Infante; Rahayu Mardikaningsih (Journal of Social Science Studies (JOS3), 2022)
Business activities using internet technology are an innovative way of conducting company activities. By utilizing internet technology, companies can conduct various business activities electronically such as business transactions, operational company functions, share information with consumers and suppliers to maintain relationships before, during and after the purchase process. Business people need effective marketing media with the aim of expanding their market share. Social media as a marketing tool is certainly related to marketing communications. This research was conducted to determine the effectiveness of social media as an online business marketing medium. This research is a qualitative research by conducting a literature study related to social media and online business promotion. The results of the study show that the use of social media makes it easier for business people with reduced costs. but with all the advantages, business people still have to have a preventive attitude when conducting business transactions.